PENGARUH JOB INVOLVEMENT DAN PERSONALITY TERHADAP SAFETY PERFORMANCE PADA ABK KRI TNI ANGKATAN LAUT - Safira Alvionisa; Gartinia Nurcholis; Dessy Nur Utami (Jurnal Psikologi Poseidon, 2022)
The purpose of this study was to determine the effect of job involvement and personality on the safety performance of Indonesia Navy Ship Crew. This study uses a quantitative approach. The population in this study amounted to 95. The sampling technique in this study was stratified random sampling. Based on the results of data analysis that has been carried out on the major hypothesis testing, the significance value in the anova table is 0.000 is less than 0.05, so it can be concluded that job involvement and personality jointly affect the safety performance of Indonesia Navy Ship Crew. In the results of the major hypothesis test, it was also found that the R Square value was 0.185, so it can be concluded that the effect of the job involvement and personality variables together on the safety performance of the crew of the Indonesia Navy Ship Crew is 18.5%. In the results of the minor hypothesis test, it was found that the effective contribution of job involvement to safety performance was 10.1% and the effective contribution of personality to safety performance was 17.8%, while the remaining 82.2% was influenced by other variables not included in the study.